Severe injuries in elite Korean male wrestlers: a comparison study between wrestling styles - Yoo, S.; Yoon, S.; Song, M. (The Korean Journal of Sports Medicine, 2024)
Purpose: This study aimed to examine the experience of severe knee, shoulder, and ankle injuries in elite Korean male wrestlers, focusing on a comparison between Greco-Roman (GR) and freestyle (FS) wrestling. Methods: A total of 90 wrestlers (46 GR and 44 FS aged 24.8±3.7 years) who participated in the national team selection tournament voluntarily participated in this study, selected by random sampling. A standardized questionnaire was used to collect data on severe injuries to the knee, shoulder, and ankle that resulted in a time loss of =3 weeks. Results: Approximately 41% of all participants experienced severe injuries to the knee, 21% to the shoulder, and 30% to the ankle. FS wrestlers were significantly more likely to experience severe knee injuries than GR wrestlers (p<0.001), and they tended to require more time to return to play. Significant differences in specific maneuvers that caused severe knee (p<0.001), shoulder (p=0.011), and ankle (p=0.002) injuries were observed by wrestling style. Conclusion: The current findings indicate that the patterns of severe injuries in wrestling may vary by wrestling style, emphasizing the importance of developing wrestling style-specific injury prevention and management strategies.